Factors That Influence The Nurse Performanceinpatienroom At Rumah Sakit Umum Daerah Haji Abdul Manan Simatupang 2022 - Roby Pranata; Donal Nababah; Johansen Hutajulu (Jurnal Keperawatan dan Fisioterapi, 2023)
Nursesasoneofhealthworkersinthehospitalhavinganimportantrolein achieving health development goals. The success of health services depends ontheparticipation of nursesto providehighqualitycare nursingfor patients .